Heat exchange between non-insulated barn and the ground in experimental research - Bieda, Wacław; Radoń, Jan; Nawalany, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
The paper presents the results of two-year studies conducted in real operating conditions of a non-insulated and unheated barn for 120 cows. As a result, it was possible to determine temperature fields in the ground beneath the floor and around the building, as well as to define heat flux directions. It was concluded that there is no analogy between temperature fields and heat flux directions with the heated buildings. In colder periods of the year, the heat accumulated in the ground is emitted to the inside of the building; in the summer, the ground absorbs the excess of heat from the building. The final conclusion was that the foundations should be insulated vertically.